Estimating the benefits of obesity prevention on productivity: an Australian perspective - Menon, Kirthi; de Courten, Barbora; Ademi, Zanfina; Owen, Alice J.; Liew, Danny; Zomer, Ella (International Journal of Obesity, 2022)
Background/objectives Obesity poses one of the biggest public health challenges globally. In addition to the high costs of obesity to the healthcare system, obesity also impacts work productivity. We aimed to estimate the benefits of preventing obesity in terms of years of life, productivity-adjusted life years (PALYs) and associated costs over 10 years. Subjects/methods Dynamic life table models were constructed to estimate years of life and PALYs saved if all new cases of obesity were prevented among Australians aged 20–69 years from 2021 to 2030. Life tables were sex specific and the population was classified into normal weight, overweight and obese. The model simulation was first undertaken assuming currently observed age-specific incidences of obesity, and then repeated assuming all new cases of obesity were reduced by 2 and 5%. The differences in outcomes (years of life, PALYs, and costs) between the two modelled outputs reflected the potential benefits that could be achieved through obesity prevention. All outcomes were discounted by 5% per annum. Results Over the next 10 years, 132 million years of life and 81 million PALYs would be lived by Australians aged 20–69 years, contributing AU$17.0 trillion to the Australian economy in terms of GDP. A 5% reduction in new cases of obesity led to a gain of 663 years of life and 1229 PALYs, equivalent to AU$262 million in GDP. Conclusions Prevention of obesity is projected to result in substantial economic gains due to improved health and productivity. This further emphasises the need for public health prevention strategies to reduce this growing epidemic.